Investment Commitments in Europe and Central Asia Doubled in 2007 - Izaguirre, Ada Karina; Mirzagalyamova, Alfiya (World Bank, Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation in Europe and Central Asia amounted to US$45.5 billion in 2007, reaching a new peak, according to just-released data from the private participation in infrastructure project database. Europe and Central Asia accounted for 29 percent of the year's total investment commitments in developing countries, a larger share than any other developing region. Investment commitments in the region were almost twice those in 2006, thanks both to new projects and to projects implemented in previous years. The 43 new projects accounted for US$21.3 billion, while projects reaching financial closure in 1990-2006 attracted US$24.2 billion. Investment in physical assets increased by almost 75 percent to US$32 billion, accounting for 70 percent of the year's investment in the region. Payments to the government (such as divestiture revenues and spectrum or concession fees) amounted to US$13.6 billion, the second highest level in the region in 1990-2007.